Awareness Level of Internal and External Stakeholders’ Participation in the Implementation of Sustainable School Programs and Projects: Input to Effective Stakeholders Management Plan - Millano, Generosa D.; Callo, Eden C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Stakeholders were an important element in any institution, especially in the educational arena. It was composed of teachers, guardians, students, and local government units who play meaningful roles in achievinga quality education, affordable education, school performance as well as resources. This study aimed to assess the awareness level of internal and external stakeholders’ participation in the implementation of sustainable school programs and projects, input to effective stakeholders’ management. This paper used descriptive-correlational research designed. There were 1,198 respondents, were female, high school level, age 11-15 years old, and occupation belong to stay at home parent, unemployed, students, retired. Stakeholders perceived the level of awareness was “moderate” while they “agreed” with stakeholders’ management plan and “much effective” on the implementation of sustainable school programs and projects. This study revealed that there is a significant relationship between the awareness level of both internal and external stakeholders’ participation as well as the stakeholders’ management plan to the sustainability of school programs and projects. There is a significant difference between the awareness level of internal and external stakeholders’ participation and their perceived level of implementation to sustain the school programs and projects. The stakeholders’ management plan also predict that it has a significant effect on the awareness of stakeholders’ participation and the sustainability of school programs and projects.